AUTHENTIC ASSESMENT IN WRITING - Sri Sarwanti (TRANSFORMATIKA, 2015)
When talking about teaching and learning, assesment is also discussed to know how far the process achieves its goals. What kind of assesment teachers use will depend on the material they transfer to their students. There are several kinds of assesment. Since the paradigm in education is shifted, the way teachers asses their students’ performance is also shifted as well. Therefore nowadays authentic assesment is broadly introduced, learned, and applied in most teaching learning process.Since the paradigm in education has shifted, the way teachers assess the students’ writing is shifted as well following the new paradigm beyond constructivism. More and more rubrics are set to exactly show the real condition and processes of the writing itself.Authentic assessment in writing plays a very important role in its teaching since the impact will be huge to the students. The process of this assessment really show the students’ performance. Key words: authentic assessment, paradigm shift, writing